2018
DOI: 10.1186/s13054-018-2077-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polymyxin B hemoperfusion on modulation of human leukocyte antigen DR in severe sepsis patients

Abstract: BackgroundRecent randomized trials have not found that polymyxin B hemoperfusion (PMX-HP) improves outcomes for patients with sepsis. However, it remains unclear whether the therapy could provide benefit for highly selected patients. Monocyte human leukocyte antigen (mHLA-DR) expression, a critical step in the immune response, is decreased during sepsis and leads to worsening sepsis outcomes. One recent study found that PMX-HP increased mHLA-DR expression while another found that the treatment removed HLA-DR-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 38 publications
1
45
2
1
Order By: Relevance
“…The biology of endotoxin in humans is characterised by movement through different compartments, which presumably could occur following LPS removal by the PMX cartridge. Srisawat et al recently demonstrated a similar finding with modulation of HLA-DR that was statistically significant in patients with septic shock treated with PMX versus sham, but again no significant difference in post-treatment EAA [ 27 ].…”
Section: Discussionmentioning
confidence: 79%
“…The biology of endotoxin in humans is characterised by movement through different compartments, which presumably could occur following LPS removal by the PMX cartridge. Srisawat et al recently demonstrated a similar finding with modulation of HLA-DR that was statistically significant in patients with septic shock treated with PMX versus sham, but again no significant difference in post-treatment EAA [ 27 ].…”
Section: Discussionmentioning
confidence: 79%
“…196 Recently, the immunomodulation effect of PMX-HP has been reported in another RCT by improvement of monocyte and neutrophil functions in patients with sepsis without a benefit in mortality or renal outcome. 197…”
Section: Experimental Therapies For S-akimentioning
confidence: 99%
“…PMX-DHP increases surface antigen HLA-DR and CD16 expression on granulocytes, helping immune cells to recovery from immunoparalysis [11]. In this case report, we obtained the resolution of pathology by assembling rapidly conventional surgical therapy and hemoperfusion therapy with immobilized PMX-B cartridges, even though there was no recommendation for this treatment and there was a lack of literature.…”
Section: Discussionmentioning
confidence: 99%